The siege / 4. - Lasky, Kathryn (Lasky, Kathryn. Guardians of Ga'Hoole, 2004)
Soren is called upon by the elders of the Great Ga'Hoole Tree to lead a crew of spies into St. Aegolius Academy for Orphaned Owls and escape undetected in order to gain the information the noble owls need to fend off an attack by Kludd and the Pure Ones.